Human immunodeficiency virus accelerates brain aging and disrupts the trajectory of glymphatic clearance in aging brain - Nguchu, Benedictor Alexander; Zhao, Jing; Lu, Yu; Han, Yifei; Jin, Han; Wang, Xiaoxiao; Li, Hongjun; Shaw, Peter (Frontiers in Psychiatry, 2025)
IntroductionExisting evidence indicates that HIV enters the nervous system in the early days of infection. However, the involvement of HIV in the pathogenesis of key biological aspects of the brain, such as glymphatic clearance and brain aging, and its role in explaining complex phenomena like motoric and executive dysfunction, remains unrecognized.MethodsHerein, we recruited 145 subjects to study the brain aging using brain-predicted age differences (brain-PADs) and investigate how HIV affects the typical trajectory of glymphatic clearance in aging brain. The assessment of glymphatic clearance in the aging brain was performed using a technique called "diffusion tensor image analysis along the perivascular space” (DTI-ALPS). We further evaluated the association between accelerated brain aging trajectories and cognitive performance to explain impairments observed in motor and executive functions in people living with HIV. ResultsOur results showed that subjects with HIV had increased brain-PAD in several brain structures compared to those who were HIV-negative, suggesting underlying neuropathology associated with HIV. The brain structures demonstrating accelerated aging (increased brain-PAD) include the middle frontal gyrus, pre-and post-central gyri, supramarginal gyrus, precuneus, cuneus, parietal lobule and operculum, and superior and middle occipital gyri of the left hemisphere. While normal subjects maintained typical trajectories of glymphatic clearance (as measured by the DTI-ALPS index) with age or brain-PADs for several structures, including the left central operculum, left frontal operculum, left opercular inferior frontal gyrus, and left triangular inferior frontal gyrus, none of these trajectories were maintained in subjects with HIV. Our data also show that increased brain-PAD in brain regions was associated with lower performance in motor and executive functions. DiscussionThese findings suggest that HIV infection accelerates brain aging and disrupts the trajectory of glymphatic clearance in aging brain, which may explain the complex mechanisms underlying cognitive impairment in motor and executive domains often seen in HIV patients. These new insights may shift our understanding of HIV pathology and aid the development of new therapeutic targets, contrary to previous approaches.